Efficacy, Safety, and Long-Term Continuation of Vaginal Pessaries for Pelvic Organ Prolapse: A Systematic Review and Meta-Analysis - Heristanto; Rahajeng (HM Publisher, 2026)
Background: Pelvic organ prolapse (POP) represents a profound failure of pelvic floor anatomy, significantly impairing patient quality of life through complex functional and anatomical derangements. Vaginal pessaries stand as the primary conservative intervention. However, the contemporary literature remains fragmented regarding their long-term adherence kinetics and comparative pathophysiological efficacy against definitive surgical reconstruction. Methods: A systematic review and meta-analysis were conducted, adhering strictly to PRISMA 2020 guidelines. Major scientific databases, including PubMed, Scopus, and Cochrane CENTRAL, were systematically searched for randomized controlled trials and prospective cohorts published between 2016 and 2026. Data synthesis employed a random-effects model, calculating Standardized Mean Differences (SMD) for validated symptom scores and pooled prevalence for longitudinal continuation and adverse events. Results: Seven major studies comprising 2,772 participants were included. The pooled short-term continuation rate under twelve months was 76.6% (95% CI 68.2–85.0%), which demonstrated a predictable decline to 53.4% (95% CI 45.1–61.7%) beyond one year. Meta-analysis of validated symptom scores (PFDI-20) demonstrated a robust, transformative reduction in prolapse distress (SMD -1.24; 95% CI -1.56 to -0.92, p < 0.0001), showing statistical equivalence to surgical outcomes in advanced prolapse cohorts. Adverse events were uniformly mild, dominated by vaginal discharge (pooled prevalence 18.6%) and occult stress incontinence (11.4%). Conclusion: Vaginal pessaries provide a high magnitude of pathophysiological symptom relief that parallels surgical correction in the short to medium term. By biomechanically restoring the pelvic axes, pessaries neutralize visceral nerve traction. While long-term continuation inevitably declines due to behavioral fatigue, the superior safety profile establishes pessaries as a definitive therapeutic modality.